Autologous adipose-derived mesenchymal stem cells and hydroxyapatite for bone defect in rabbits - Franco, Guilherme Galhardo [UNESP]; Minto, Bruno Watanabe [UNESP]; de Paula Coelho, Livia [UNESP]; Malard, Patricia Furtado; Carvalho, Elizabeth Regina [UNESP]; Kawamoto, Fernando Yoiti Kitamura [UNESP]; de Alcantara, Brenda Mendonca [UNESP]; Dias, Luis Gustavo Gosuen Goncalves [UNESP] (Czech Academy of Agricultural Sciences, 2022)
This study aims to evaluate the effect of autologous adipose-derived mesenchymal stem cells (AAD-MSC), with and without synthetic absorbable hydroxyapatite (HAP-91), on the bone regeneration in rabbits. Thirty-four female white New Zealand rabbits were submitted to a 10 mm distal diaphyseal radius ostectomy, divided into 3 experimental groups according to the treatment established. The bone gap was filled with 0.15 ml of a 0.9% saline solution containing two million AAD-MSC (G1), or AAD-MSC associated with HAP-91 (G2). The control group (CG) received only 0.15 ml of the 0.9% saline solution. Radiographs were made post-operatively, and after 15, 30, 45 and 90 days. Fifty percent of the samples were submitted to a histological examination at 45 days and the remaining ones at 90 days post-operatively. Radiographically, the periosteal reaction, bone callus volume and bone bridge quality were superior in G2 (P < 0.05). Histologically, the bone repair was faster and more efficient in G1 at 45 days (P < 0.05). In conclusion, AAD-MSC improved the regeneration on the experimentally induced bone defects in rabbits; however, the use of hydroxyapatite requires caution given the granulomatous reaction produced in the species.
Keywords: Adipose derived MSC; Cell transplantation; Fracture healing; Oryctolagus cuniculus